Production of Leucaena leucocephala seedlings using mineral and organic mineral fertilizer (Research, Society and Development, 2021)
Phosphate fertilization promotes the development of forest seedlings. Thus, studies on means of adding organic and inorganic phosphorus (P) are necessary to promote the quality of Leucena (Leucaena leucocephala) seedlings. Therefore, the objective was to evaluate the initial growth and quality of Leucena seedlings submitted to doses of mineral and organic mineral fertilizers. The Leucena plants were fertilized with two fertilizers being: mono-ammonium-phosphate (MAP) (9% N and 48% P2O5) and an organic mineral (OM) (11% N and 26.6% P2O5, 18.2% Organic Carbon) and four doses of P2O5 (0; 10; 20 and 30 mg kg-1), with three repetitions. At 60 days after planting were evaluated: plant height (AP), stem diameter (DC), aerial biomass (BMPA), root biomass (BMR), aerial dry mass (MSPA), dry mass of the root (MSR), robustness quotient (ROB) and Dickson's Quality Index (IQD). The means of AP, DC and IQD were not influenced by the sources and doses of P, but the means BMPA, BMR, MSPA, MSR and ROB showed significant influence for sources and doses of P. The mineral fertilizer promotes better effect in the variables of the biomass of the aerial part and the organic mineral favors the biomass of the root. There were positive corrections between the parameters evaluated for Leucena seedling: BMPA, BMR, MSPA, MSR and IQD, and ROB showed a negative correlation with DC.